2016
DOI: 10.1111/jth.13188
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector computed tomographic pulmonary angiography in patients with a high clinical probability of pulmonary embolism

Abstract: computed tomographic pulmonary angiography in patients with a high clinical probability of pulmonary embolism. J Thromb Haemost 2016; 14: 114-20. EssentialsWhen high probability of pulmonary embolism (PE), sensitivity of computed tomography (CT) is unclear. We investigated the sensitivity of multidetector CT among 134 patients with a high probability of PE. A normal CT alone may not safely exclude PE in patients with a high clinical pretest probability. In patients with no clear alternative diagnosis after CTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
(25 reference statements)
0
24
0
2
Order By: Relevance
“…A total of 3143 publications were retrieved from our literature search. Both primary reviewers finally agreed to include 22 articles in the final analysis [2,7,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (quadratic weighted kappa 0.692 [95% CI, 0.543-0.840]). The reasons for exclusion are described in Fig.…”
Section: Literature Search and Agreementmentioning
confidence: 99%
“…A total of 3143 publications were retrieved from our literature search. Both primary reviewers finally agreed to include 22 articles in the final analysis [2,7,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (quadratic weighted kappa 0.692 [95% CI, 0.543-0.840]). The reasons for exclusion are described in Fig.…”
Section: Literature Search and Agreementmentioning
confidence: 99%
“…On the other side of the spectrum, some studies and clinical guidelines suggest that patients with a high pretest probability of PE should undergo additional testing even if their CTPA is negative. 17,18 This remains a matter of debate, but based on recent data, physicians should not hesitate to order a leg CUS whenever a patient with a high pretest probability of PE presents with signs or symptoms of DVT. 18 Another use of pretest probability is to guide therapeutic management while waiting for the results of diagnostic tests.…”
Section: Clinical Use Of the Pretest Probability For Suspected Vtementioning
confidence: 99%
“…17,18 This remains a matter of debate, but based on recent data, physicians should not hesitate to order a leg CUS whenever a patient with a high pretest probability of PE presents with signs or symptoms of DVT. 18 Another use of pretest probability is to guide therapeutic management while waiting for the results of diagnostic tests. The American College of Chest Physicians guidelines on antithrombotic therapy suggest that patients should receive anticoagulant therapy while awaiting the results of diagnostic tests if they have a high pretest probability of VTE, if they have an intermediate probability and tests are expected to be delayed for more than 4 hours, and if there is a low pretest probability and tests will not be performed within 24 hours.…”
Section: Clinical Use Of the Pretest Probability For Suspected Vtementioning
confidence: 99%
“…Moores et al recently performed a prospective noninterventional study to assess the safety of CTPA (64row) to exclude PE in outpatients presenting to the emergency department of an academic center in Madrid with suspected PE and a high pretest clinical probability as assessed by the three-level Wells rule. Among 134 patients with a high clinical probability and a negative CTPA finding, seven were diagnosed with VTE either by another test at baseline (n = 5) or during a 3-month follow-up (n = 2), corresponding to an overall 'failure rate' of CTPA alone of 5.2% (95% CI 1.5-9.0%) [7]. The authors thus concluded that CTPA alone may not safely exclude PE in patients with a high clinical probability.…”
Section: Introductionmentioning
confidence: 99%